High‐pressure behavior of (Cs, K)Al4Be5B11O28 (londonite): A single‐crystal synchrotron diffraction study up to 26 GPa. Issue 10 (21st June 2017) - Gatta, Giacomo Diego; Lotti, Paolo; Comboni, Davide; Merlini, Marco; Vignola, Pietro; Liermann, Hanns‐Peter
Abstract: The compressional behavior and the P ‐induced deformation mechanisms at the atomic scale of (Cs, K)Al4 Be5 B11 O28 (londonite, a ~7.31 Å and space group P 4 ¯ 3 m ) were investigated by in situ single‐crystal synchrotron X‐ray diffraction with a diamond anvil cell up to 26 GPa. No phase transition was observed within the P ‐range investigated: this material exhibits isotropic compression (i.e., with cubic symmetry) in response to the applied pressure. Fitting the P–V data with a Birch‐Murnaghan isothermal equation of state, we obtained: V 0 =390.8(3) Å 3, K P0 =212(7) GPa (β0 =1/ K P0 =0.0047(1) GPa −1 ) and K ′=4.6(6). A series of structural refinements, based on the high‐pressure intensity data, were performed. The stiffness of londonite (similar to that of carbides) is governed by its close‐packing structure, and in particular by the very low compressibility of B‐ and Be‐tetrahedra and the modest compressibility of the Al‐octahedra. The Cs‐polyhedra are the most compressible units of the structure. The effects of pressure can be accommodated by intrapolyhedral compression or deformation, leading to a modest bulk compression. The high amount of boron in londonite (B2 O3 ~50 wt%) makes its synthetic counterpart a potential neutron absorber. In addition, the high content of Cs makes londonite‐type materials as potential hosts for nuclear waste.